Relationships between Nutritional Status, Beverage Consumption Habits, and Disease Frequency in High School Students - Yunieswati, Wilda; Kushargina, Rosyanne; Rizqiya, Fauza (Jurnal Gizi dan Pangan, 2023)
This study aimed to analyze the relationship between nutritional status, beverage consumption habits, and disease frequency in high school students. Data were collected through an online questionnaire to explore the characteristics of the subjects: weight, height, beverage consumption habits, and disease frequency. The subjects were 78 students at SMA Muhammadiyah 25 Pamulang, Banten. This study has discovered nutritional status and nutritious beverage consumption habits are not related to disease frequency (p>0.05). Meanwhile, herbal beverage consumption habits are related to disease frequency (p<0.05). The herbal drink contains antioxidants that can improve immunity and cause less frequent disease.